The Foundation of the All-Round Security of Intelligent Vehicles is Digital Security - Zuo, Yixin; Li, Jianming; Tian, Ru; Zhang, Fan (International Journal of Computer Science and Information Technology, 2026)
As intelligent vehicles evolve from AI-enabled tools to intelligent entities with autonomous interaction capabilities, security boundaries are no longer confined to traditional mechanical protection, but extend to the all-domain scenario where data flows, algorithm operations, network communications and location services interweave and coexist. Therefore, digital security technology serves as the core support for intelligent transformation and the technical cornerstone that underpins the all-domain security. In this context, digital security can empower the upgrading of traditional security systems and enable the leap from "passive protection" to "active prevention".